Proactive Personality as a Predictor of Career Adaptability and Career Growth Potential: A View From Conservation of Resources Theory - Wang, Su; Mei, Mei; Xie, Yang; Zhao, Yiting; Yang, Fu (Frontiers in Psychology, 2021)
In the present study, we offered a new account for the development of career adaptability and the realization of career growth potential based on conservation of resources (COR) theory. Using data collected from 903 university students in China, we examined how and when proactive personality influences students’ career adaptability and career growth potential by introducing emotional exhaustion as a mediator as well as friend support and teacher individualized consideration as boundary conditions. Specifically, the results confirmed a positive effect of proactive personality on career adaptability, with this relationship mediated by emotional exhaustion. In addition, results suggested a positive effect of proactive personality on career growth potential, with this relationship mediated by emotional exhaustion and career adaptability. Moreover, results showed that in-school social support (i.e., friend support and teacher individualized consideration) served as moderators in the relationship between proactive personality and emotional exhaustion, such that the negative effect of proactive personality on emotional exhaustion was strengthened when students received high levels of social support. Theoretical implications of career adaptability research and COR theory and practical implications for promoting adaptability resources and career growth in university are provided.